Immune responses of a meningococcal A + W outer membrane vesicle (OMV) vaccine with and without aluminium hydroxide adjuvant in two different mouse strains. Issue 11 (20th September 2016) - Tunheim, Gro; Arnemo, Marianne; Næss, Lisbeth M.; Norheim, Gunnstein; Garcia, Luis; Cardoso, Daniel; Mandiarote, Aleida; Gonzalez, Domingo; Sinnadurai, Kalpana; Fjeldheim, Åse‐Karine; Bolstad, Karin; Rosenqvist, Einar
Abstract : Meningococci ( Neisseria meningiditis) of serogroups A and W have caused large epidemics of meningitis in sub‐Saharan Africa for decades, and affordable and multivalent vaccines, effective in all age groups, are needed. A bivalent serogroup A and W (A + W) meningococcal vaccine candidate consisting of deoxycholate‐extracted outer membrane vesicles (OMV) from representative African disease isolates was previously found to be highly immunogenic in outbred mice when formulated with the adjuvant aluminium hydroxide (AH). OMV has been shown to have inherent adjuvant properties. In order to study the importance of AH and genetical differences between mice strains on immune responses, we compared the immunogenicity of the A + W OMV vaccine when formulated with or without AH in inbred C57BL/6J and BALB/cJ mice (Th1 and Th2 dominant strains, respectively). The immunogenicity of the vaccine was found to be comparable in the two mice strains despite their different immune profiles. Adsorption to AH increased anti‐OMV IgG levels and serum bactericidal activity (SBA). The immune responses were increased by each dose for the adsorbed vaccine, but the third dose did not significantly improve the immunogenicity further. Thus, a vaccine formulation with the A and W OMV will likely benefit from including AH as adjuvant.